A novel approach to assessing the bioavailability of biopeptide inhibitor of HMG CoA reductase from germinated and ungerminated Kara Kratok (Phaseolus lunatus L.) - Cahyo Budiyanto; Andriati Ningrum; Agnes Murdiati; Retno Indrati (PeerJ)
Background The bioavailability of biopeptide compounds is a development challenge, mainly because of their resistance to the digestion system. This study aimed to determine the bioavailability of HMG CoA reductase biopeptide inhibitors from germinated and ungerminated Kara Kratok (Phaseolus lunatus L.). Methods Germinated and ungerminated brown P. lunatus were simulated for digestion enzyme in vitro (120 minutes for pepsin and pancreatin), followed by an in situ method for absorption. Perfusate samples were measured for the absorption percentage, inhibition of HMG CoA reductase, molecular weight (MW), peptide concentration, and hydrolysis degree (%DH). Results The results showed that germinated brown P. lunatus exhibited the highest absorption (32.42%), and the percentage of HMG CoA reductase inhibition during enzymatic digestion was at 210 minutes (87.51%), with MW < 10 kDa, peptide concentration of 2.39 mg/mL, and %DH of 48.90%. These findings suggest that germinated brown P. lunatus is a potent HMG CoA reductase inhibitor with significantly higher bioavailability than that of its ungerminated counterpart. This finding underscores its superiority in this context and open new possibilities for biopeptide research.